Drug trafficking, organized crime, and violence in the Americas today - Bagley, Bruce Michael; Rosen, Jonathan D. (University Press of Florida, 2015)
Preface: On the study of drug trafficking and organized crime networks in Latin America and the Caribbean in the twenty-first century -- Introduction. drug trafficking and organized crime in Latin America and the Caribbean in the twenty-first century: challenges to democracy / Bruce M. Bagley -- U.S. drug policies at home and abroad -- Coca, cocaine, and consumption: trends and antitrends / J. Bryan Page -- Illegal drugs as a national security threat: securitization of drugs in the U.S. official discourse / Yulia Vorobyeva -- The war on drugs and the role of southcom / Juan Gabriel Tokatlian -- Mission creep: the U.S. military's counterdrug role in the Americas / Adam Isacson -- Security challenges at the U.S.-Mexican border: understanding the security threats to state and local governments / Rocío A. Rivera Barradas -- Drug-control policies in the United States: patterns, prevalence, and problems of drug use in the United States / Bruce M. Bagley -- Drug trafficking and organized crime: country and regional analyses -- Colombia -- Colombia and its wars against drug trafficking, 1970-2010 / Elvira María Restrepo -- Illicit drugs in the Colombia-U.S. relationship: review and prospects / Arlene B. Tickner and Carolina Cepeda -- Escalating heroin consumption and the spread of HIV in Colombia: an emerging public health threat / Clyde McCoy, Daniel H. Ciccarone, Zelde Espinel Ben-Amy, Jeanene McCoy Bengoa, Oscar Bernal, Duane C. McBride, and James M. Shultz -- Bolivia -- Bolivian drug policy under the Morales Administration / Marten W. Brienen -- Peru -- The vicious cycle: the resurgence of drug production and drug trafficking in Peru / Marten W. Brienen and Jonathan D. Rosen -- Mexico, Central America, and the Caribbean -- In search of the M¿rida initiative: from antecedents to practical results / Alberto Lozano-Vázquez and Jorge Rebolledo Flores -- Police reform in Mexico: a never-ending story / Sigrid Arzt -- Democracy, security, and organized crime in Central America